Learning Sanskrit to Strengthen Multiculturalism and Religious Moderacy - Surada, I Made; Subagia, I Nyoman; Sura Adnyana, Putu Eka (International Journal of Engineering, Science and Information Technology, 2025)
This paper discusses Sanskrit language learning as a strategic instrument in strengthening the values of multiculturalism and religious moderation in Indonesia. Sanskrit has not only historical value as a heritage of Hindu-Buddhist civilization but also contains universal teachings such as dharma, Ahimsa, tat twam asi, and vasudhaiva kutumbakam, which are relevant in the context of a plural society. Through a qualitative approach with observation, Documentation, and literature study methods, this research shows that Sanskrit learning can shape the character of students who are tolerant, inclusive, and have a nationalistic outlook. The learning model developed is contextual, dialogical, and collaborative and integrates the values of diversity and interfaith understanding. Despite facing challenges such as the stigma of exclusivism, limited teachers, and low motivation to learn, learning Sanskrit remains relevant for character education and strengthening social cohesion. Therefore, innovative pedagogical strategies and inclusive curriculum policies are needed so that Sanskrit can contribute significantly to building a harmonious Indonesian society with diversity.